Communication Barriers and the Clinical Recognition of Diabetic Peripheral Neuropathy in a Diverse Cohort of Adults: The DISTANCE Study. Issue 5 (3rd May 2016) - Adams, Alyce S.; Parker, Melissa M.; Moffet, Howard H.; Jaffe, Marc; Schillinger, Dean; Callaghan, Brian; Piette, John; Adler, Nancy E.; Bauer, Amy; Karter, Andrew J.
Abstract : The purpose of this study was to explore communication barriers as independent predictors and potential mediators of variation in clinical recognition of diabetic peripheral neuropathy (DPN). In this cross-sectional analysis, we estimated the likelihood of having a DPN diagnosis among 4, 436 patients with DPN symptoms. We controlled for symptom frequency, demographic and clinical characteristics, and visit frequency using a modified Poisson regression model. We then evaluated 4 communication barriers as independent predictors of clinical documentation and as possible mediators of racial/ethnic differences: difficulty speaking English, not talking to one's doctor about pain, limited health literacy, and reports of suboptimal patient–provider communication. Difficulty speaking English and not talking with one's doctor about pain were independently associated with not having a diagnosis, though limited health literacy and suboptimal patient–provider communication were not. Limited English proficiency partially attenuated, but did not fully explain, racial/ethnic differences in clinical documentation among Chinese, Latino, and Filipino patients. Providers should be encouraged to talk with their patients about DPN symptoms, and health systems should consider enhancing strategies to improve timely clinical recognition of DPN among patients who have difficult speaking English. More work is needed to understand persistent racial/ethnic differences in diagnosis.